Digital Philology and Manuscript Sustainability: A Semantic Annotation Model for Classical Arabic Texts - Stanislaus, Surip; Abdallah, Mona (Journal of Humanities Research Sustainability, 2025)
Background. The sustainability of classical Arabic manuscripts is often confined to digitization efforts that focus solely on image preservation and limited text markup. These approaches do not fully address the semantic richness and epistemological structure inherent in Islamic intellectual heritage. Purpose. This study aims to develop a semantic annotation model tailored for classical Arabic texts to support digital philology and enrich manuscript sustainability through machine-readable and concept-linked interpretations. Method. Using a developmental qualitative research design, three classical manuscripts were annotated semantically using a custom-built model based on RDF and Islamic ontology. The model was evaluated by domain experts in philology and computational linguistics, focusing on four criteria: semantic accuracy, contextual relevance, interoperability, and usability. Results. The model achieved annotation accuracy above 91% across all manuscripts. Experts rated semantic precision (4.7/5) and contextual relevance (4.6/5) as its strongest aspects. The system successfully mapped technical terms and logical concepts within classical texts and linked them across manuscripts. A case study demonstrated the model’s effectiveness in identifying relationships between epistemological terms and enabling thematic exploration. Conclusion. This semantic annotation model advances digital philology by enabling structured, concept-based analysis of classical Arabic texts. It bridges computational methods with Islamic textual traditions and opens new pathways for collaborative, sustainable, and meaningful engagement with manuscript heritage.